Mechanisms of Vagus Nerve Stimulation in Improving Motor Dysfunction After Stroke - Cai X; Jiang J; Zhou G; Zhang Y (Neuropsychiatric Disease and Treatment)
Xiaohu Cai,1,* Jiayao Jiang,2,* Guochao Zhou,3,* Yelei Zhang4 1Department of Rehabilitation Medicine, Xishan People’s Hospital of Wuxi City, Wuxi Branch of Zhongda Hospital Southeast University, Wuxi, People’s Republic of China; 2Department of Orthopedics, The 904th Hospital of the Joint Logistics Support Force of the PLA, Wuxi, Jiangsu, People’s Republic of China; 3Department of Orthopedics, The Army 947th Hospital, Kashgar, People’s Republic of China; 4Department of Neurosurgery, Xishan People’s Hospital of Wuxi City, Wuxi Branch of Zhongda Hospital Southeast University, Wuxi, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yelei Zhang, Department of Neurosurgery, Xishan People’s Hospital of Wuxi City, Wuxi Branch of Zhongda Hospital Southeast University, Wuxi, People’s Republic of China, Email Zhangyelei2019@163.comAbstract: Patients with stroke would have persistent functional deficits despite undergoing physiotherapy and rehabilitation training. Recently, vagus nerve stimulation (VNS), a newly emerging neuroregulatory technique, has been shown to improve motor dysfunction after stroke. Evidence from clinical and preclinical studies has proven the safety, feasibility, and efficacy of invasive and noninvasive VNS. It has been reported that the positive effect may be related to anti-inflammatory effects, mediating neuroplasticity, increasing blood–brain barrier integrity, promoting angiogenesis and reducing spreading depolarization. However, the underlying mechanism remains poorly understood. In this review, we have summarized the potential molecular mechanisms by which VNS promotes stroke prognosis. We believe that VNS combined with upper-extremity rehabilitation can improve impairment and function among moderately to severely impaired stroke survivors. The applications and further exploration are discussed to provide new insights into this novel therapeutic technique.Keywords: vagus nerve stimulation, stroke, neuroinflammatory response, brain plasticity